Do NSAIDs affect bone healing rate, delay union, or cause non-union: an updated systematic review and meta-analysis - Chuang, Po-Yao; Yang, Tien-Yu; Tsai, Yao-Hung; Huang, Kuo-Chin (Frontiers in Endocrinology, 2024)
Nonsteroidal anti-inflammatory drugs (NSAIDs) may potentially result in delayed or non-union of fractures by inhibiting prostaglandin synthesis. However, studies have provided conflicting results. This systematic review and meta-analysis aimed to gather and synthesize current evidence on the potential influence of NSAIDs on bone healing.We searched the PubMed, Embase and Cochrane CENTRAL databases for relevant studies published up to July 25, 2023. Specific keywords were: "NSAID," "nonsteroidal anti-inflammatory drug," "cyclooxygenase-2 inhibitor," "bone healing," "non-union," "pseudoarthrosis," "delayed union," and "atrophic bone". Prospective, retrospective, and case-controlled studies assessing the correlation between NSAID use and bone healing outcomes were eligible for inclusion. The leave-one-out approach was used to test the robustness of the meta-analysis results. Twenty studies with a total of 523,240 patients were included in the analysis. The mean patient age ranged from 6.7 to 77.0 years, and follow-up duration ranged from 3 to 67 months.Meta-analysis revealed no significant difference in non-union or delayed union between NSAIDs user and non-user (pooled adjusted odds ratio [OR] = 1.11, 95% confidence interval [CI]: 0.99-1.23). The initial analysis identified a significant association between NSAID usage and an increased risk of reoperation. However, this association became insignificant upon conducting sensitivity analyses (crude OR = 1.42, 95% CI: 0.88-2.28). In conclusions, NSAIDs may have a minimal impact on non-union or delayed union risks, though interpretative caution is advised due to the limited number of studies and the absence of specific focus on NSAID types and dosages.